2020
DOI: 10.1039/d0sc04542j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic generation of alkoxy radicals from unfunctionalized alcohols

Abstract: Alkoxy radicals have long been recognized as powerful synthetic intermediates with well-established reactivity patterns. Due to the high bond dissociation free energy of aliphatic alcohol O–H bonds, these radicals are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(82 citation statements)
references
References 143 publications
0
81
0
1
Order By: Relevance
“…For example, the formation of oxygen-centred radical 107 results in ketone formation and C-C bond fragmentation leading to products such as 108. 105 Incorporation of a nickel catalyst facilitated cross-coupling reactions between sulfonyl radicals 109 and bromobenzene and this led to coupled products such as 110. 106 Amidyl radicals 113 can partake in 5-exo-trig cyclisation, followed by further radical functionalisation and this gave lactams such as 114.…”
Section: Summary Of Radical Coupling Reactionsmentioning
confidence: 99%
“…For example, the formation of oxygen-centred radical 107 results in ketone formation and C-C bond fragmentation leading to products such as 108. 105 Incorporation of a nickel catalyst facilitated cross-coupling reactions between sulfonyl radicals 109 and bromobenzene and this led to coupled products such as 110. 106 Amidyl radicals 113 can partake in 5-exo-trig cyclisation, followed by further radical functionalisation and this gave lactams such as 114.…”
Section: Summary Of Radical Coupling Reactionsmentioning
confidence: 99%
“…Specially, iron may be a good catalyst candidate, which can perform both CÀ H bond oxidation [25,26,28] and oxidative CÀ C bond cleavage [43] through photocatalysis. [44][45][46][47][48][49] Iron halides, especially FeCl 3 , were found to catalyze the photo-oxidation of sp 3 CÀ H bonds of alkanes and arylalkanes with oxygen. The system was well studied by Shul'pin et al and Takaki et al [25] Recently, Jiang and co-workers developed a tetrahalogenoferrate(III) complex to enable the benzylic CÀ H oxidation under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Suárez group demonstrated that alkoxy radicals could be generated from nonprefunctionalized alcohols using molecular iodine and hypervalent iodine reagents 24–26 . The radical translocation of the generated alkoxy radicals delivers a C ‐centered radical by exploiting a 1,5‐hydrogen atom transfer (1,5‐HAT) process 27–32 . Despite the important contributions of the aforementioned works, most synthetic methods have been focused on the C─N bond formation, and the examples for the formation of the intramolecular C─O bonds driven by visible‐light photoredox catalysis are still limited (Scheme 1(a)).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] The radical translocation of the generated alkoxy radicals delivers a C-centered radical by exploiting a 1,5-hydrogen atom transfer (1,5-HAT) process. [27][28][29][30][31][32] Despite the important contributions of the aforementioned works, most synthetic methods have been focused on the C─N bond formation, and the examples for the formation of the intramolecular C─O bonds driven by visible-light photoredox catalysis are still limited (Scheme 1 (a)). 33 From the perspective of green and sustainable chemistry, the development of metal-free photoreactions has attracted increased interest.…”
Section: Introductionmentioning
confidence: 99%